Decolonizing "Prehistory" Deep Time and Indigenous Knowledges in North America - Mackenthun, Gesa; Mucher, Christen (2021)
Decolonizing "Prehistory" combines a critical investigation of the documentation of the American deep past with perspectives from Indigenous traditional knowledges and attention to ongoing systems of intellectual colonialism. Bringing together experts from American studies, archaeology, anthropology, legal studies, history, and literary studies, this interdisciplinary volume offers essential information about the complexity and ambivalence of colonial encounters with Indigenous peoples in North America, and their impact on American scientific discourse. The chapters in this book reveal how anthropology, archaeology, and cultural heritage have shaped the collective ideological construction of Indigenous cultures, while actively empowering the voices that disrupt conventional tropes and narratives of "prehistory." Constructions of America's ancient past-or the invention of American "prehistory"-occur in national and international political frameworks, which are characterized by struggles over racial and ethnic identities, access to resources and environmental stewardship, the commodification of culture for touristic purposes, and the exploitation of Indigenous knowledges and histories by industries ranging from education to film and fashion. The past's ongoing appeal reveals the relevance of these narratives to current-day concerns about individual and collective identities and pursuits of sovereignty and self-determination, as well as to questions of the origin-and destiny-of humanity. Decolonizing "Prehistory" critically examines and challenges the paradoxical role that modern scholarship plays in adding legitimacy to, but also delegitimizing, contemporary colonialist practices. Contributors: Rick Budhwa, Keith Thor Carlson, Kirsten Matoy Carlson, Jessica Christie, Philip J. Deloria, Melissa Gniadek, Annette Kolodny, Gesa Mackenthun, Christen Mucher, Naxaxalhts'i (aka Sonny McHalsie), Jeff Oliver, Mathieu Picas, Daniel Lord Smail, Coll Thrush